O staropolskim wzorcu gospodarza raz jeszcze z punktu widzenia historyka (w świetle poradników rolniczych z XVI i XVII w.) - Świderska-Włodarczyk, Urszula (Studia Europaea Gnesnensia, 2015)
The aim of this paper is to reconstruct the figure of a model nobleman-farmer in the 16th- and 17th-century Poland. As a research tool, the author employs an original definition of the model, while relying on farming almanacs from the period as sources. Using this as a basis, the author demonstrates that the model significantly departed from the image conveyed by the literature of the period.